2017
DOI: 10.1186/s12936-017-1867-z
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-treated durable wall lining (ITWL): future prospects for control of malaria and other vector-borne diseases

Abstract: While long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS) are the cornerstones of malaria vector control throughout sub-Saharan Africa, there is an urgent need for the development of novel insecticide delivery mechanisms to sustain and consolidate gains in disease reduction and to transition towards malaria elimination and eradication. Insecticide-treated durable wall lining (ITWL) may represent a new paradigm for malaria control as a potential complementary or alternate longer-lasting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
(105 reference statements)
2
18
0
Order By: Relevance
“…Modifications to bed net design may make them more user-friendly within the small shelters of displaced populations. Alternatively, indoor residual spraying (IRS) could be used; however IRS can be operationally challenging and economically unsustainable [ 1 , 45 47 ]. Within Birambizo IDP camp, IRS was carried out when NGOs were permanently operating within the camp, however violent conflict has interrupted NGO efforts at maintaining IRS interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifications to bed net design may make them more user-friendly within the small shelters of displaced populations. Alternatively, indoor residual spraying (IRS) could be used; however IRS can be operationally challenging and economically unsustainable [ 1 , 45 47 ]. Within Birambizo IDP camp, IRS was carried out when NGOs were permanently operating within the camp, however violent conflict has interrupted NGO efforts at maintaining IRS interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One other possible vector control method that could be well suited to the IDP camp setting is the use of insecticide-treated tarpaulin for IDP shelters. A recent review [ 45 ] highlights evidence suggesting the effectiveness of insecticide-treated durable wall lining over multiple years, however phase III trials are still underway to provide evidence as to the operational implementation of this novel vector control method within displaced populations [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study suggest that IRS should include kitchens and verandas in addition to the inside walls of houses. Alternatively, novel control methods such as insecticide-treated durable wall linings 26 , spatial repellents [27][28][29] , insecticidal paints or screening to mosquito-proof verandas and kitchens could be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Subsequent research showed that the product was well accepted by users and could serve as a complement to LLINs. [3,[10][11][12] The ITWL offers several logistical advantages over IRS. The ITWL's expected multi-year e cacy avoids the complexity of repeated rounds of application in the same and successive years.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In spite of this de ciency, a future ITWL could potentially be effective against malaria and other vector borne diseases. [10] However, the usefulness of an ITWL also depends on its cost and comparison with alternative approaches. Thus, this paper rst reports the economic cost of installing and removing ITWL in the Muheza trial.…”
Section: Introductionmentioning
confidence: 99%